UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA KELAS V SDN MAWAR 7 BANJARMASIN: Penelitian Tindakan Kelas (PTK) - Erika Aulia Winanda; Irnanda Dewi Setyowati; Maulia Dwiyanti; Muhammad Mahdiannoor; Muhammad Zaini; Namira; Nor Amalia Shaleha; Rohana; Selvi Apriyani; Yunita; Drs. Mahmuddin, M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low activity and learning outcomes of fifth-grade students in Mathematics at SDN Mawar 7 Banjarmasin. Only 9 out of 25 students (36%) achieved the minimum mastery criteria (KKTP) of 70, with a class average of 44. This Classroom Action Research (CAR) aimed to improve student activity and learning outcomes through the implementation of the Problem Based Learning (PBL) model. The study was conducted collaboratively in two cycles, involving 25 fifth-grade students during the even semester of the 2025/2026 academic year. Data were collected through observation, written tests, and documentation, and analyzed using descriptive comparative methods. The results showed significant improvement: student activity increased from 52% (Quite Active) in Cycle I to 84% (Very Active) in Cycle II. Learning outcomes improved from 36% in the pre-cycle to 52% in Cycle I, and reached 80% in Cycle II, meeting the established success indicator. These findings demonstrate that the PBL model effectively creates an active, collaborative, and meaningful learning environment that enhances both student participation and academic performance in Mathematics.